(untitled) (Biological Sciences - PJSIR, 2003)
Soil incubation experiment was conducted to study some aspects of phosphorus (P) cycling in soil series of Peshawar Valley. Phosphorus adsorption before and after incubation was studied, physico-chemical properties and AB-DTPA extractable P were determined. Soil samples containing 19 to 22% (w/w) moisture were incubated at 25°C for 7 weeks. The amount of P adsorbed by the soil from KH2PO4 solution (0 to 50 ?g/ml) before and after incubation was calculated by the difference between the amount of P in solution after 24 h shaking and the initially amount was present. These soils contain CaCO3, which might adsorb organic P, or form insoluble Ca phosphates. The adsorption isotherm plots highlight the ability of these soils for P sorption. Soil having high amount of CaCO3 and clay have more affinity for P adsorption in the soil system.